Use of TIC´s as a management strategy for the development of competitiveness (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2009)
Citizens of most countries of the world are demanding increasingly better access to public services, seeking prompt and timely responses suitable to their growing needs. The Internet seems to be the management tool of public sector response. So establish contact points directly to its citizens. It is necessary to comply with such an event. Many transactions will be conducted on the platform that delivers network of networks, and are precisely those that represent them to governments and the private sector, a real challenge. For example, the power of taxation by countries traditionally applied internally, seems to have no effect against cyberspace, making the task of tax collection more difficult. The aim of this work is to establish, based on common practices at theinternational level, measures that might contribute to the management in designing a strategy to provide the citizens of Latin America Net infrastructure enabling efficient transactions offer translated into cost savings, time and services highly improved. The methodology used for this work is biographical-documentary, based on the revised text, recent research and legal rulesdeveloped by international bodies such as the OECD. The aim is to arrive at results that allow us to conclude that the use of ICTs by management, represents a successful strategy that allows organizations to increase their competitiveness
Keywords: internet; competitiveness; management; cyberspace; OECD